2021
DOI: 10.1016/j.celrep.2021.109039
|View full text |Cite
|
Sign up to set email alerts
|

The molecular landscape of neural differentiation in the developing Drosophila brain revealed by targeted scRNA-seq and multi-informatic analysis

Abstract: The Drosophila type II neuroblast lineages present an attractive model to investigate the neurogenesis and differentiation process as they adapt to a process similar to that in the human outer subventricular zone. We perform targeted single-cell mRNA sequencing in third instar larval brains to study this process of the type II NB lineage. Combining prior knowledge, in silico analyses, and in situ validation, our multi-informatic investigation describes the molecular landscape from a single developmental snapsh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 77 publications
1
26
0
Order By: Relevance
“…Fig. 2D), and we identified several other unique marker genes for each subtype (Ariss et al , 2020; Brunet Avalos et al , 2019; Cattenoz et al , 2016; Estacio-Gomez et al , 2020; Michki et al , 2021)(Suppl. Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Fig. 2D), and we identified several other unique marker genes for each subtype (Ariss et al , 2020; Brunet Avalos et al , 2019; Cattenoz et al , 2016; Estacio-Gomez et al , 2020; Michki et al , 2021)(Suppl. Fig.…”
Section: Resultsmentioning
confidence: 87%
“…To determine clusters, marker genes of each cluster were identified by FindAllMarkers function (Seurat) and logistic regression analysis (Scanpy). Based on canonical markers and gene expression profiles, genes similar clusters were merged and annotated based on existing knowledge and literature (Ariss et al , 2020; Brunet Avalos et al , 2019; Cattenoz et al , 2016; Estacio-Gomez et al , 2020; Michki et al , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…It is unclear whether the spatial organization and migration of radial glia during division—which are important in mammalian neurogenesis—are a conserved feature of Drosophila neurogenesis. However, recent studies have demonstrated that the neuroblast pool is highly heterogenous [ 85 , 86 , 87 ], hinting that spatial patterning may be more important in Drosophila than is currently understood. While tll can reprogram type I neuroblasts into type II neuroblasts, it is only successful in ≈60% of type I lineages [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the embryonic CNS and OL, relatively fewer TTFs have been identified in Type II NBs in the CB. Type II NBs were specifically labelled and FACS sorted to perform Type II NB-specific scRNA-seq analyses [ 28 ]. The pseudotime analysis confirmed the temporal cascade of TTFs in INPs proposed in the previous genetic studies [ 19 , 20 ].…”
Section: Temporal Patterning Of Neuroblasts and Intermediate Progenit...mentioning
confidence: 99%